1980
DOI: 10.2307/3280806
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ammonium in Amino Acids by Trypanosoma cruzi

Abstract: Ammonium ions were incorporated into L-glutamate and alpha-ketoglutarate in epimastigote forms of Trypanosoma cruzi through the following enzymatic systems: NADPH and NADH-dependent glutamate dehydrogenase, NADPH-dependent glutamate synthase, L-glutamine synthetase and NADH-dependent glutamate synthase in order of decreasing specific activity (mumoles of product formed/min/mg protein). The pH optima and Km's for the glutamate dehydrogenase system were determined. Disc electrophoresis showed the presence of cat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

1
9
0
8

Year Published

1981
1981
2005
2005

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 15 publications
(18 citation statements)
references
References 16 publications
1
9
0
8
Order By: Relevance
“…As TAT catalyses a reversible transamination among aspartate or alanine and the aromatic amino acids, it seems to be also a key enzyme in the biosynthesis of these amino acids. Both isoforms of glutamate dehydrogenase also participate in the biosynthesis of amino acids by their ability to incorporate NH 3 into α-ketoglutarate yielding glutamate [50]. It was also shown that glutamine can be synthesized from glutamate and NH 3 in the presence of glutamine synthetase [50].…”
Section: Major L-amino Acid Anabolic and Catabolic Pathways In T Cruzimentioning
confidence: 97%
“…As TAT catalyses a reversible transamination among aspartate or alanine and the aromatic amino acids, it seems to be also a key enzyme in the biosynthesis of these amino acids. Both isoforms of glutamate dehydrogenase also participate in the biosynthesis of amino acids by their ability to incorporate NH 3 into α-ketoglutarate yielding glutamate [50]. It was also shown that glutamine can be synthesized from glutamate and NH 3 in the presence of glutamine synthetase [50].…”
Section: Major L-amino Acid Anabolic and Catabolic Pathways In T Cruzimentioning
confidence: 97%
“…(SILBER et al, 2005). Esta enzima pode participar também na biossíntese de aminoácidos ao incorporar amônia a alfa-cetoglutarato gerando glutamato (CALDAS et al, 1980).…”
Section: Metabolismo De Proteínas E Aminoácidosunclassified
“…TAT catalisa também uma transaminação reversível entre aspartato ou alanina e os aminoácidos aromáticos pelo qual parece ter também uma função chave na biossíntese destes aminoácidos. Glutamina também pode ser sintetizada a partir de glutamato e amônia pela glutamina sintase (CALDAS et al, 1980 (BURSELL et al, 1996).…”
Section: Metabolismo De Proteínas E Aminoácidosunclassified
“…Como a TAT catalisa uma transaminação reversível entre aspartato ou alanina e aminoácidos aromáticos, parece ser uma enzima chave na biosíntese desses aminoácidos. Ambas as isoformas de glutamato desidrogenase também participam da biosíntese de aminoácidos pela sua habilidade de incorporar NH 3 no α-ketoglutarato gerando glutamato (Caldas et al, 1980). O aspartato é um dos compostos que induz a diferenciação de epimastigotas para tripomatigotas metacíclicos (metaciclogênese), sendo transportado por ambas as formas do parasita.…”
Section: B) Metabolismo Do Aspartatounclassified
“…A glutamina pode ser sintetizada a partir do glutamato e NH 3 na presença de glutamina sintetase (Caldas et al, 1980). Como esta reação é reversível, a glutamina pode ser oxidada pela via glutamato.…”
Section: C) Metabolismo Da Glutaminaunclassified